Estudo dinâmico de fluidos magneto-reológicos de baixo custo - Kuramoto, Pedro Paulo (Universidade Federal de São Carlos, 2019)
Magnetorheological (MR) fluids are materials composed of magnetizable particles suspended in a non-magnetizable “carrier” fluid. These materials have the ability to change their rheological properties in the presence of a magnetic field. Due to this characteristic, these fluids have been studied for engineering applications. To carry out this work, an MR fluid was synthesized in a simple way with low-cost materials, to be used in the tests, in order to verify the influence of the magnetic field on the damping effect of this synthesized fluid. For this purpose, tests were carried out without and with the magnetic field, the application of the magnetic field was generated by permanent neodymium magnets. As a result, it was obtained that the MR fluid composed of oil and toner has the ability to change the damping coefficient in the presence of a magnetic field. From this it was concluded that an MR fluid made from oil and toner could have applications in engineering in the future, thus enabling the reduction of the cost of equipment that uses this fluid.
Dynamic study of low-cost magnetorheological fluids
Keywords: Fluido magneto-reológico; Amortecedores; Campo magnético; Vibrações; Sistemas dinâmicos; ENGENHARIAS::ENGENHARIA MECANICA::MECANICA DOS SOLIDOS